Effect of 1-(1-naphthylmethyl)-piperazine on antimicrobial agent susceptibility in multidrug-resistant isogenic and veterinary Escherichia coli field strains - Marchetti, María Laura (2012)
The objective of this study was to evaluate the interaction of the efflux pump inhibitor 1-(1-naphthylmethyl)-piperazine (NMP) when combined with different families of antimicrobial agents against isogenic strains and multidrug-resistant (MDR) Escherichia coli field strains isolated from animals. Laboratory isogenic strains of E. coli with different levels of expression of efflux pumps were used as quality controls. Ten MDR E. coli strains were collected from healthy animals in a cross-sectional study in four commercial dairy farms. The MICs of florfenicol, ciprofloxacin, tetracycline and ampicillin were determined by a serial microdilution method in Luria-Bertani broth in the presence or absence of NMP. NMP used with ampicillin exerted no effect on the isogenic or field strains. In most of the field MDR E. coli strains and in an acrAB-overexpressing (AG112) isogenic strain, the MICs of florfenicol, ciprofloxacin and tetracycline decreased at least fourfold when the antimicrobial was combined with the highest NMP concentrations. In the wild-type strain (AG100), there were no decreases of more than twice the MIC, whilst in strain AG100A, an efflux pump-deficient strain, the MIC did not change, regardless of the concentration of NMP used with these three antimicrobials. Thus, ampicillin was not affected by the efflux pump mechanism, whereas ciprofloxacin, tetracycline and florfenicol were shown to be substrates of efflux pumps, with a consequent significant reduction in MICs. Resistance could not be completely reversed in the E. coli field strains by NMP, probably because other resistance mechanisms were also present. However, in strain AG112, the MIC results demonstrated that NMP expressed an important synergistic activity with florfenicol. The reduction in florfenicol MIC value was sufficient to reverse antimicrobial resistance completely for AG112.